The antiglycation activity test of peel off mask containing gold nanoparticles synthesized from kacip fatima extract (Labisia pumilla) - Ong, Putri Stephanie; Abdulah, Sutriyo; Vardhani, Afifah Kusuma (Faculty of Pharmacy, Universitas Pancasila, 2025)
Skin aging, which is influenced by intrinsic and extrinsic factors, can accelerate skin damage, with one of the main mechanisms being the glycation reaction that results in Advanced Glycation End Products (AGEs). AGEs are the result of indirect reaction between reducing sugars and amino acids, lipids, or proteins. This reaction is also known as the glycation reaction or the Maillard reaction. This research aims to develop a peel-off mask based on gold nanoparticles synthesized with Kacip Fatima extract as an anti-aging agent. Gold nanoparticles have the potential to inhibit the formation of AGEs and improve skin quality. In this study, gold nanoparticles were synthesized by the green synthesis method using Kacip Fatima extract as a reducing agent. The method used for gold characterization is by measuring the wavelength and absorbance, polydispersity index, and zeta potential value of gold nanoparticles. The method used for antiglycation is by using microplate reader, which is stored for 3 days and tested with excitation wavelength of 365 nm and emission wavelength of 415-445 nm. The characterization results showed that the gold nanoparticles had an average size of about 79.61 nm at week 0 and increased to 101.1 nm at week 9. Glycation testing revealed that masks with 20% gold nanoparticles inhibited glycation by up to 95%, higher than the concentration of 10%. This study successfully synthesized gold nanoparticles using Kacip Fatimah extract as a reducing agent, with particles ranging from 79.61 nm to 101.1 nm over 9 weeks. The nanoparticles showed antiglycation effects, with 10% nanoparticles inhibiting glycation by 78%, suggesting potential for environmentally friendly cosmetic applications like peel-off masks.